The effects of environmental sustainability orientation on the sustainable performance, the mediating role of green supply chain management and moderating role of environmental collaboration: Evidence from Algeria - Mohamed Knouch; Hamza Lefkir; Hassan Ali Alqahtan (Decision Science Letters)
The purpose of this study is to investigate the direct effects of environmental sustainability orientation (ESO) on green supply chain management (GSCM), ESO on sustainable performance (SP), and GSCM on sustainable performance (SP). It also examines the indirect effect of GSCM on SP through the mediating role of GSCM. Moreover, it tests the moderating role of environmental collaboration (EC) between GSCM and SP. A total of 155 survey questionnaires were collected from firms with ISO 14000 certification in the manufacturing sector in Algeria. The gathered data was examined using (PLS-SEM) model. The findings showed positive effects between ESO, GSCM, and SP. However, no such effect was detected for the moderating role of environmental collaboration on the links between GSCM and SP. The limitation of this study was the use of only firms with ISO 14000 certification, so future studies should consider a wider range of firms and different scales. Regarding environmental problems, firms in Algeria can apply ESO and GSCM to achieve sustainable performance.